The Effect Of Macroeconomic Variables And Sukuk Issuance Value On Profitability Of Sharia Commercial Banks In Indonesia - Muslikhati - Muslikhati (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2023)
The growth and development of bank financial institutions is largely determined by the level of profitability resulting from their operational activities. This study aims to find out how the influence of bank external factors in the form of macroeconomic variable indicators consisting of inflation, bi-rate, exchange rate, economic growth, and bank internal factors in the form of the value of issuance of sukuk. This study uses a quantitative method, with multiple linear regression analysis. The results of the study indicate that together the variables of inflation, exchange rate bi-rate, economic growth, and the value of sukuk issuance have a significant effect on profitability. While partially the inflation variable has a significant negative effect on profitability, bi-rate has a negative and insignificant effect on profitability, the exchange rate has a significant negative effect on profitability, economic growth has a positive and significant effect on profitability, and the value of sukuk issuance has a negative and insignificant effect on profitability Commercial Sharia Banks in Indonesia for the 2010-2020 period.